An analysis of anthropomorphological characteristics of participants in the 2008 European football championship - Joksimovic, A.; Smajic, M.; Molnar, S.; Stankovic, D. (Serbian Journal of Sports Sciences, 2009)
Contemporary football tends to place more and more demand on football players with regard to the appropriate body structure, strong, enduring bodies, extensive football intelligence, controlled aggressiveness, highly developed functional and motor abilities, and a sense for improvisation and collective play. The aim of this research is to define the average values for all the 368 participants in the 2008 European Football Championship by analyzing basic anthropomorphological parameters, as well as certain body indices. The research results point to the fact that the average height of all the participants in the 2008 European Football Championship was 182.97 ± 6.59cm and the average body mass was 77.88± 6.98 kg. The tallest average was noted in goalkeepers, followed by defense and forwards players, while the lowest values for height (179.02 ± 5.94 cm) and body mass (73.89 ± 5.81 kg) were noted in midfield players. Body height and body mass in elite football players have increased in the course of time, and it is also noticeable that apart from forwards, each particular position requires a particular body type.